The “Tower Of Babel” Of Modernity and the Future Prospects of a Nation State - Radžvilas, Vytautas (Politologija, 2018)
[only abstract in English; full article and abstract in Lithuanian]This article discusses the future prospects of nations and nation states in the era of globalization by critically analyzing the theoretical justifications of the philosophical idea that one of the inevitable consequences of globalization is a gradual disintegration of nations and nation states. The origins of this idea are traced back to the political theory of Immanuel Kant, particularly to Kant’s vision of a cosmopolitan, civil society and the concept of the worldwide confederation of republican states. The article introduces an argument that the position that Kant’s vision of the civil society and confederation of states is internally incoherent and utopian, and it should be viewed as a normative moral and political ideal (or, in Kantian terms, a maxim of the practical historical reason that every human being should strive for) rather than as a theoretically coherent and justified political project. This normative ideal of modernity is viewed as the driving force of history, since it facilitates attempts to implement it in practice and achieve the end result – a peaceful, global civil society. In such a state of peaceful coexistence, the nation, as a form of political organization, loses its relevance, and the nation state gets replaced by a cosmopolitan confederation of republican states.The modern vision of a cosmopolitan and apolitical global order is viewed as one of the most important ideas of political philosophy, which has a tremendous influence on the history and geopolitical development of the modern world. It is shown that, for over two centuries, this idea has been both a theoretical and an ideological inspiration for global governance projects. The article suggests that a conceptual “overlap” between the two conceptions of a nation – the traditional natural law and the modern constructivist one – may have been one of the primary reasons of why this idea has retained philosophical and political significance for over two centuries. The article defends the view that this conceptual confusion led to a theoretically and empirically unjustified conviction that the disintegration of nations and nation states will be an inevitable outcome of the development of the modern world, and that this conviction facilitates further political experiments aimed at realizing the utopian apolitical society.
Keywords: none